Instructional interactive whiteboard materials: Designers' perspectives - Turel, Yalin Kilic; Demirli, Cihad (Elsevier Science Bv, 2010)
The purpose of this research is to examine the design and development process of instructional materials that can be used through interactive whiteboards (IWBs) in terms of three critical aspects - software selection, IWB features, and teaching methods and techniques. For this study in which 80 instructional designer candidates participated, a number of Interactive Whiteboard Materials (IWB-Ms) were designed for a variety of disciplines including mathematics, medicine, engineering, social studies, and music by groups of designers. At the end of five-week design process, participants were given a questionnaire consisted of open-ended questions regarding their IWB-M design. The qualitative data were examined in terms of software and tools that were utilized, supported IWB features, and instructional methods and techniques that would be employed along with the IWB-Ms' use. (C) 2010 Published by Elsevier Ltd.
1st World Conference on Learning, Teaching and Administration (WCLTA) -- OCT 29-31, 2010 -- Amer Univ, Cairo, EGYPT
Keywords: Instructional design; interactive whiteboards; interactive whiteboard materials; interactive whiteboard software; material design; instructional designer candidate